Increased risk of cancer in patients with systemic lupus erythematosus. Issue 4 (April 1992) - Pettersson, T; Pukkala, E; Teppo, L; Friman, C
Abstract : To evaluate the risk of cancer in patients with systemic lupus erythematosus (SLE) a series of 205 consecutive patients (182 women and 23 men) were followed up for cancer through the files of the Finnish Cancer Registry. The follow up consisted of a total of 2340 person years. Fifteen cancers were diagnosed against 5.7 expected (relative risk (RR) 2.6, 95% confidence interval (CI) 1.5 to 4.4). Among the women there were four non-Hodgkin's lymphomas against 0.09 expected (RR 44, CI 11.9 to 111) and two soft tissue sarcomas against 0.04 expected (RR 49, CI 6.0 to 177). When evaluated by a case control study previous treatment with cytostatic drugs showed no influence on the occurrence of cancer in this series of patients with SLE.